2004
DOI: 10.1099/00207713-54-6-2441-a
|View full text |Cite
|
Sign up to set email alerts
|

Shewanella pacifica sp. nov., a polyunsaturated fatty acid-producing bacterium isolated from sea water

Abstract: ErrataShewanella pacifica sp. nov., a polyunsaturated fatty acid-producing bacterium isolated from sea water

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Ivanova et al (2003) reported and characterized new bacteria of the genus Shewanella (Shewanella waksmanii) isolated from the marine sipuncula. In other investigation, Ivanova et al (2004) characterized Shewanella pacifica, a polyunsaturated fatty acid-producing bacterium isolated from seawater.…”
Section: Discussionmentioning
confidence: 98%
“…Ivanova et al (2003) reported and characterized new bacteria of the genus Shewanella (Shewanella waksmanii) isolated from the marine sipuncula. In other investigation, Ivanova et al (2004) characterized Shewanella pacifica, a polyunsaturated fatty acid-producing bacterium isolated from seawater.…”
Section: Discussionmentioning
confidence: 98%
“…The carnitine levels in soil and water may vary depending on the bacterial flora at the site and whether the bacteria inhabiting those environments are capable of carnitine metabolism. The presence and utility of carnitine in the environment is supported, in part, by the number of bacteria capable of carnitine metabolism, including a few newly identified species such as Burkholderia caribensis (Achouak et al, 1999), Bacillus decisifrondis (Zhang et al, 2007), Pseudomonas kilonensis (Sikorski et al, 2001) from soil, and Shewanella pacifica from sea water (Ivanova et al, 2004).…”
Section: Carnitine In the Environmentmentioning
confidence: 99%
“…Table 1. Differential characteristics of strains A3F-7 T and ssthio04PA2-7c (Paramoritella gen. nov.) and related genera Data for reference genera were taken from the following studies: Urakawa et al (1998), Nogi et al (1998b), Nogi & Kato (1999), Benediktsdó ttir et al (2000), Lunder et al (2000), Xu et al (2003) and Kim et al (2008) (Moritella); Bowman et al (1997), Bowman (2005), Nogi et al (1998a), Venkateswaran et al (1999), Leonardo et al (1999), Ivanova et al (2001Ivanova et al ( , 2003Ivanova et al ( , 2004a, Bozal et al (2002), Skerratt et al (2002), Brettar et al (2002, Satomi et al (2003Satomi et al ( , 2006Satomi et al ( , 2007, Yoon et al (2004a, b), Toffin et al (2004), Xu et al (2005), Zhao et al (2005Zhao et al ( , 2006Zhao et al ( , 2007 …”
Section: Description Of Paramoritella Alkaliphila Sp Novmentioning
confidence: 99%